Cryptosporidiosis in a Zoonotic Gastrointestinal Disorder Perspective - Thivya Balendran; Devika Iddawela; Sajanee Lenadora (Journal of Tropical Medicine)
Cryptosporidium infection is highly prevalent among immunocompromised patients with Acquired Immunodeficiency Syndrome, cancer, primary immunodeficiency, and organ transplant recipients. Comprehensive knowledge about Cryptosporidium infection provides the means for efficient diagnosis, treatment, and prevention. Therefore, with the objective of providing an in-depth analysis of Cryptosporidiosis in immunocompromised patients, this review presents a comprehensive understating of the prevalence, risk factors, pathophysiology of Cryptosporidium infection, clinical presentation in the immunocompromised, the immune response of the host, diagnostic methods performed in laboratory settings, possible treatments, and prevention methods, which can be used for further studies. Peer-reviewed, published, original articles on cryptosporidiosis in immunocompromised patients were searched using specific key-words on PubMed, ResearchGate, Google Scholar, and ScienceDirect databases. Articles which were accessible to the date of 18th of August 2023, were included in this comprehensive review. We analyzed reports on Cryptosporidium in immunocompromised patients with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS), cancer, primary immunodeficiency, and organ transplant recipients. 134 Articles describing epidemiology, related risk factors, clinical presentation, diagnosis, and possible treatments in the light of pathogenesis, pathophysiology, and virulence factors of Cryptosporidium and immunology of the host are summarized in this study. Effective treatments to be administered, importance, and ways of prevention were identified. Cryptosporidium infection was found to be highly prevalent among immunocompromised in Asia, Africa, Europe, and North America. The immunity of the host and the decrease in CD4+ T-cell count were found to the main factors which decide the susceptibility and the severity of infection. Drugs that activate host immunity and suppress Cryptosporidium growth, along with supportive therapy, is an effective treatment. But prevention is the most effective strategy for immunocompromised patients; thus, a better understanding about the disease would lead to effective prevention.